The information management of the projects - Vasile Creț (Agora International Journal of Economical Sciences (AIJES), 2016)
Methodologically A\^~point of view, the management of a company is studied based on the systems, methods, methodologies and techniques (general and specific) that the managers apply to fulfill the managerial functions. The managerial tool consists of systems, methods and management techniques that appeal to managers for foresight exercise, organization, coordination, assessment and control. Informal subsystem is perfect adapted to the profile of the organization. It is integrated in the informational system of the mother company, being advantaged, because of its physical distance between locations, the electronic communications in detriment of paper. This fact implies the existences of a very good communication infrastructure.The main characteristic of a project is its newness. A project is a walk in unknown, full of risks and uncertainness. There are no two identical projects and even a project which repeats will be every time different in one or more commercial, administrative, social, politics or physic aspects.
Keywords: 330